'Words, Words, Words': Making Comics and Sense of the Three Texts of Hamlet. Issue 1 (2nd January 2023) - Cop, Michael; Large, David
ABSTRACT: In teaching our first-year university students to understand what Shakespearean language is and what it does, we asked them to edit the three different early modern editions of Hamlet and then adapt their edits into a comics spread. Using some of the numerous graphic novel adaptations of Shakespeare and a platform that we forked from Willian Carvalho's 2012 project 'comicgen', our first-year university students create their own visual representations of Shakespearean dialogue. This article explores the early modern texts that often coalesce to form a modern edition of Hamlet, the many Shakespearean graphic novels available today, the pedagogical comics platform created for our students, and the results of our pedagogical project.